Strategic intelligence for the future. - Dou, Henri; Juillet, Alain; Clerc, Philippe, 1954- (Innovation, entrepreneurship and management series., 2019)
Information in all its forms is at the heart of the economic intelligence process. It is also a powerful vector of innovation and, more than ever, a balance between economic and societal forces. That is why a large part of Strategic Intelligence for the Future 2 analyzes the various aspects of information, from traditional processing and research to the psychological and epigenetic aspects of its development. This leads to a new vision of its integration into organizations. In addition, new technologies offer extensive access to information, including social networks which are critically analyzed here. In a complex world where geopolitics and the new concept of information warfare are becoming increasingly important, it becomes imperative to better apprehend and understand our environment, in order to develop critical thinking that will reinforce the different global aspects of security in economic intelligence.